Compact Liquid Crystal Based Tunable Band-Stop Filter with an Ultra-Wide Stopband by Using Wave Interference Technique - Longzhu Cai; Huan Xu; Daping Chu (International Journal of Antennas and Propagation)
A wave interference filtering section that consists of three stubs of different lengths, each with an individual stopband of its own central frequency, is reported here for the design of band-stop filters (BSFs) with ultra-wide and sharp stopbands as well as large attenuation characteristics. The superposition of the individual stopbands provides the coverage over an ultra-wide frequency range. Equations and guidelines are presented for the application of a new wave interference technique to adjust the rejection level and width of its stopband. Based on that, an electrically tunable ultra-wide stopband BSF using a liquid crystal (LC) material for ultra-wideband (UWB) applications is designed. Careful treatment of the bent stubs, including impedance matching of the main microstrip line and bent stubs together with that of the SMA connectors and impedance adaptors, was carried out for the compactness and minimum insertion and reflection losses. The experimental results of the fabricated device agree very well with that of the simulation. The centre rejection frequency as measured can be tuned between 4.434 and 4.814 GHz when a biased voltage of 0–20 Vrms is used. The 3 dB and 25 dB stopband bandwidths were 4.86 GHz and 2.51 GHz, respectively, which are larger than that of other recently reported LC based tunable BSFs.